Novas, antigas e extraordinárias: os jornais cearenses e a construção narrativa nos faits divers criminais (1850-1890) - Silva, Nicodemos Zacarias Oliveira da (2024)
This research seeks to analyze newspapers from Ceará, especially those with greater circulation and longevity during the second half of the 19th century. Our main objective is the narrative elaboration about crime, violence and the unusual, through criminal faits divers, as an editorial strategy for political combat, control of morality, ordering of behavior and literary composition. During this period, the creation of spaces within periodicals, focused on entertainment, such as news columns, variety shows, serials, advertisements and correspondence, occurred in a more blatant manner, both nationally and locally. Through these spaces, the scholars responsible for creating those texts and their readers were able to publish narratives centered on violent crimes and bizarre or curious stories that were constructed as a stimulus to reading and the circulation of those texts to the general public. Because, at the same time that infamous profiles of individuals and acts considered dangerous and harmful to the maintenance of order and morals in that society were published in an exaggerated way, seeking to generate sensations, reaffirming the condemnation of those social types, in the same way they opened space for construction of a certain leisure based on morbid and extraordinary stories. The discussion we seek to centralize here is how accessory forms of control and social adequacy over the popular classes of the province of Ceará were re-elaborated in that textual genre, but at the same time how they responded to what seemed being a growing taste among readers/listeners of that period for those macabre plots. We also tried to analyze how this search for combating normative deviation resulted in the reaffirmation of the established legal-normative order, in addition to the legitimization of the moral substrate of a traditional Catholic religious character. It is essential to understand how journalistic discourse used those stories as a guiding strategy for acceptable codes of conduct for local society, without, however, giving up the fable fabrication in which those texts were still structured. In this way, we propose to discuss how those texts became, for the most part, an instrument for maintaining hierarchies and a social ordering that reaffirmed not only notable differences of class, but of gender and race.